Navigating power dynamics and hierarchies in medical education: Enhancing faculty experiences and institutional culture - Singh, P K; Singh, S; Ahmad, S; Singh, V K; Kumar, R (Journal of postgraduate medicine, 2025)
Power dynamics in medical education, driven by leadership roles, significantly influence patient care, learning, research, and institutional growth. Hierarchies provide essential structure and mentorship, but can also suppress communication and ethical behaviour through intimidation and exclusion. This duality underscores the importance of addressing hierarchical dynamics in academic medicine. This narrative review evaluates the impact of hierarchical dynamics on faculty experiences, focusing on both positive and negative leadership behaviours. A comprehensive literature search was conducted across PubMed, Google Scholar, and ScienceDirect using terms such as "power dynamics," "hierarchical structures," and "faculty development." Articles published within the last 20 years were prioritised, with studies selected based on their empirical contribution and relevance to medical education. A thematic synthesis approach was used to identify key themes and strategies for fostering a supportive and inclusive academic culture. Hierarchies in medical education can positively influence faculty by offering structure, mentorship, and clear role expectations, which are critical for professional development. However, pervasive negative behaviours, including micromanagement, favouritism, and exclusion, were identified as major contributors to stress, burnout, and hindered professional growth among junior faculty and colleagues. Hierarchical dynamics are pivotal in shaping faculty experiences in medical education. Mitigating the adverse impacts of power imbalances requires regular behavioural audits, leadership training, and robust mentorship programs. These initiatives can foster an inclusive academic culture that prioritises open communication and equitable professional development. Future research should develop and evaluate targeted interventions to address power imbalances and improve institutional culture.